Reliability of handheld dynamometry in assessment of hip strength in adult male football players - Fulcher, M. L.; Hanna, C. M.; Raina Elly, C. (Journal of Science and Medicine in Sport, 2010)
The aim of this study was to evaluate the intra- and interrater reliability of handheld dynamometry (HHD) for measuring hip muscle strength in a sample of 30 healthy semi-professional adult male football players. The reliability of HHD had not been assessed in athletes who were likely to be stronger than populations tested previously. Maximal isometric strength of resisted hip flexion and adduction were measured. Mean strength ranged from 51.5 kg for dominant hip flexion to 26.7 kg for hip adduction at 90° of hip flexion. Intrarater reliability intraclass correlation coefficients (ICCs) ranged from 0.70 to 0.89. ICCs for interrater reliability ranged from 0.66 to 0.87. As expected, muscle strength in this group of athletes was significantly higher than that of populations in which HHD reliability has been assessed. Despite this, muscle strength testing of hip flexor and adductor muscles can be performed with good to excellent intra- and interrater reliability in this population.